Myelin and Lymphocyte Protein (MAL): A Novel Biomarker for Uterine Corpus Endometrial Carcinoma - Li D; Zhang J; Wu L; Yang X; Chen Z; Yuan J (Cancer Management and Research, 2021)
Dong Li,1,* Juan Zhang,2,* Lilong Wu,2 Xiaoming Yang,1 Zheng Chen,1 Jiangjing Yuan1 1Department of Obstetrics and Gynecology, International Peace Maternity and Child Health Hospital, Shanghai Key Laboratory of Embryo Original Diseases, Shanghai Municipal Key Clinical Speciality, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Department of Obstetrics and Gynecology, Jinan Maternal and Child Health Care Hospital, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiangjing Yuan Email drtracy80@163.comPurpose: Myelin and lymphocyte protein (MAL) plays an essential role in esophageal cancer, classic Hodgkin’s lymphoma and breast cancer. However, its role in uterine corpus endometrial carcinoma (UCEC) has not been explored. Therefore, the current study sought to explore the role of MAL in UCEC.Patients and Methods: Differentially expressed genes (DEGs) were identified by using Limma package in R based on TCGA-UCEC data. Kaplan–Meier plotter analysis was performed to explore the prognostic value of MAL. Function enrichment analyses were performed using GSVA. Further, roles of MAL in UCEC were validated using clinical cohort, which included 120 tumor and adjacent tissues. qRT-PCR and immunohistochemistry analyze the samples. Chi-square tests were performed to explore the associations between MAL expressions and clinicopathological features.Results: The findings showed that overexpression level of MAL in tumor was correlated with worse survival (p = 0.000424). MAL exhibited predictive power for survival time of UCEC patients (3 years: AUC = 0.635; 5 years: AUC = 0.635). Notably, high expression level of MAL was correlated with advanced stage of UCEC. MAL overexpression was significant in UCEC with microsatellite instability (MSI). Enrichment analysis showed that MAL was enriched mainly in MYC targets, epithelial mesenchymal transition and KRAS signaling. Furthermore, MAL was associated with infiltration of immune cells in the tumor micro-environment and immune checkpoint. Analysis showed a positive association between MAL and T cell (CD4+ memory resting). Correlation analysis showed that MAL was significantly positively correlated with several immune checkpoint, including CD274 (R = 0.3389, p = 0.0081), LAG3 (R = 0.2913, p = 0.0229), PDCD1LG2 (R = 0.5345, p < 0.0001). The prognosis value of MAL was confirmed through the experiment.Conclusion: The findings of the current study indicated that MAL is an effective prognostic biomarker and potential therapeutic target for UCEC patients. These results indicated that MAL functions as a diagnosis and therapeutic marker in UCEC treatment.Keywords: MAL, UCEC, prognosis, immune micro environment, biomarker